Characterisation of bridge-track interaction of a multi-span viaduct subjected to heavy haul loading - Mupwedi, Emilia Joyce (Department of Civil Engineering, 2023)
In many countries, railway transportation has been the primary mode of transportation, and engineers have been pushing boundaries to increase productivity and reduce costs for decades. The rail is the most important component of the railway infrastructure because it serves as the driving surface, direction guidance, and force transmission. Continuously Welded Rail (CWR), which is defined as rails that have been welded together, are now used in modern railways. When the rail is built on a bridge, the bridge's and rolling stock's behavior adds additional forces to CWR rails. As a result of the coupling effects of tracks and deformed superstructures, additional rail stresses are superimposed on other forces. These extra stresses are caused primarily by the longitudinal elongation of the superstructure as a result of temperature, braking, traction, and deck movement. The interaction of these forces between the rail and the bridge is therefore known as Track-Bridge-Interaction (TBI). Therefore, the horizontal forces must be precisely managed to prevent rail failure. This research presents a characterization of TBI for heavy haul railways and management of longitudinal forces to minimize the possibility of failure due to superimposed longitudinal forces. The Olifants River Viaduct (ORV), a 1 km long bridge with CWR and two continuous spans of 11 spans at each end and a drop span in the middle, was used as a case study in the research. The ORV has been equipped with monitoring systems to help manage the tracks. Thus, data from these systems were used to categorize the interaction forces. The research focused on categorizing the trains crossing the ORV into six (A-F) categories; the categorization was based on the train length and the commodities being hauled. The research also studied the speed variations of each train crossing the bridge. The speeds were analyzed using python and statistical tools in excel. Lastly, the impact of crossing trains on rail forces, rail temperature, ambient temperature, and deck movement was analyzed using python and statistical tools in excel. The study showed that the most frequent train to cross the bridge are category D trains with six locomotives and 342 wagons, while the train speed is dependent on the train length and the commodities hauled. Thus, the short trains in categories (A, B, and E) cross the bridge at higher constant speeds while the long trains in categories (C and D) cross the bridge at reduced speeds than the short trains but exhibit speed variations and sometimes cross the bridge at speeds exceeding the 50 km/h limit. Therefore, higher dynamic forces should be expected from short trains crossing the bridge at high constant speeds, but no additional forces should be expected on the rails from these trains as they experience no speed variations. At the same time, the long trains experience significant speed variations of both acceleration and decelerations, which imposes additional forces on the rails due to traction and braking. The imposed forces on the rails are predominantly due to crossing trains with significant speed variations of acceleration and deceleration, the acceleration change ranges from 5-30 km/h, and deceleration change ranges from 5-20 km/h. The braking and acceleration effect causes a change in the rail forces, rail temperature, and deck deflection, which in turn imposes additional forces on the rails. Therefore, high speed variation induces additional longitudinal forces on the rails. However, the imposed acceleration forces are higher than the braking forces, but the braking imposed forces are the most critical one as they tend to cause an increase in the tensile and compression forces when the forces are at their peaks, and there is a train present on the bridge, while acceleration causes a decrease in the rail forces at those times. The deck movement forces imposed on the rails were predominantly due to ambient temperature, which showed a positive linear relationship between the two. The deck expands with increasing ambient temperature and contracts with a decrease in ambient temperature. In contrast, the compression forces were within the given limits of 1100 kN, while the tension forces exceeded the rail force limit of 1400 kN when the rail temperature was between 0 − 20℃, and the deck deflection above 83 mm in the negative direction, and a present train on the bridge, making the rail more susceptible to failure during winter